2001
DOI: 10.1097/00002060-200106000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Gender-Related Differences in Maximum Shortening Velocity of Skeletal Muscle Fibers

Abstract: Both age and gender affect Vo. Age- and gender-related differences in Vo may partially explain the impairments in muscle function that occur with aging and the greater impairment in muscle function observed in OW compared with that observed in OM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
95
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 33 publications
10
95
1
3
Order By: Relevance
“…The heightened susceptibility to damage observed here, coupled with an impaired ability to recover from injury or adapt to repeated exercise reported by others (Dedrick and Clarkson 1990;McBride et al 1995;Brooks and Faulkner 1990;Rader and Faulkner 2006;Lavender and Nosaka 2006b;Cutlip et al 2006) could be a contributor to the reduced lower limb muscle strength of elderly adults. Because contraction-induced damage impairs excitation-contraction coupling and cross-bridge function (Balnave and Allen 1995;Warren et al 1994), a heightened susceptibility to injury could initiate the age-related deterioration in muscle fiber activation and contractility (Delbono et al 1995;Wang et al 2002;Larsson et al 1997;Thompson and Brown 1999;Lowe et al 2001;Frontera et al 2000;Hook et al 2001;Krivickas et al 2001). Consistent with our results, studies conducted on skinned fibers from EDL muscles of young and old laboratory rodents have identified age-related deficits at the level of the force-producing or force-transmitting components of the cell (Lynch et al 2008;Brooks and Faulkner 1996).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The heightened susceptibility to damage observed here, coupled with an impaired ability to recover from injury or adapt to repeated exercise reported by others (Dedrick and Clarkson 1990;McBride et al 1995;Brooks and Faulkner 1990;Rader and Faulkner 2006;Lavender and Nosaka 2006b;Cutlip et al 2006) could be a contributor to the reduced lower limb muscle strength of elderly adults. Because contraction-induced damage impairs excitation-contraction coupling and cross-bridge function (Balnave and Allen 1995;Warren et al 1994), a heightened susceptibility to injury could initiate the age-related deterioration in muscle fiber activation and contractility (Delbono et al 1995;Wang et al 2002;Larsson et al 1997;Thompson and Brown 1999;Lowe et al 2001;Frontera et al 2000;Hook et al 2001;Krivickas et al 2001). Consistent with our results, studies conducted on skinned fibers from EDL muscles of young and old laboratory rodents have identified age-related deficits at the level of the force-producing or force-transmitting components of the cell (Lynch et al 2008;Brooks and Faulkner 1996).…”
Section: Discussionsupporting
confidence: 87%
“…Cross-bridge kinetics are altered with aging (Larsson et al 1997;Thompson and Brown 1999;Lowe et al 2001;Frontera et al 2000;Hook et al 2001;Krivickas et al 2001) but whether these changes are directly responsible for an age-related increase in damage is unknown. Alternatively, desmin, titin, myosin light chain 2, tropomyosin, and α-actinin covary (either in concentration or isoform expression) with fiber MHC isoform content (Prado et al 2005;Chopard et al 2001;Schiaffino and Reggiani 1996) and have all been implicated in contraction-induced muscle injury (Meyer et al 2010;Lieber et al 1996;Koh and Escobedo 2004;Zhang et al 2008;Lehti et al 2007;Belcastro 1993;Childers and McDonald 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the present study we found that IIX fibers did not have age-related contractile decrements. Fiber segments studied from human quadriceps muscle biopsies show consistent slowing of V 0 with age (D'Antona et al, 2003;Krivickas et al, 2001;Larsson et al, 1997). Despite some discrepancies, overall there is a consensus that, at the cellular level, muscle shortening velocity is slowed with aging.…”
Section: Discussionmentioning
confidence: 96%
“…At the cellular level, maximal unloaded shortening velocity (V 0 ) is slower in muscle fibers from aged individuals relative to fibers from younger individuals (D'Antona et al, 2003;Degens et al, 1998;Krivickas et al, 2001;Larsson et al, 1997;Li and Larsson, 1996;Thompson, 1999;Thompson and Brown, 1999). It is well known that shortening velocity is directly related to, and dependent upon, Ca 2+ -activated myosin ATPase activity (Barany, 1967;Reiser et al, 1985).…”
Section: Introductionmentioning
confidence: 99%